A novel resistivity measurement method for a homogeneous cylinder shape based on the vdP configuration. (1st October 2022) - Ma, Deliang; Chen, Mengfei; Xie, Yifei; Feng, Huaiping; Chang, Jianmei
Abstract: The electrical resistivity method for a cylinder shape is an essential method for reflecting physical properties. However, the use of a nondestructive resistivity method with the circumferential cross-section arrangement for working components remains challenging. This paper provides a simple novel resistivity method for a cylinder shape based on the van der Pauw configuration, with four electrodes placed near the middle cross-section layer of shape. First, the theoretical solution formulae for the electrostatic potential function in the cylindrical coordinate system are derived. Then, the effect of the electrode and shape size is analysed. The results show that the electrode height is less than 1% of the cylinder height and the radian angle is less than 10°, where the electrode size effect on the correction factor (CF) can be ignored, and CF rarely depends on the cylinder shape. Finally, a prototype is designed, and the proposed method is verified in laboratory tests using geomaterials. The performance of the proposed method for fine soil at high moisture contents is found to be better than that at low moisture contents.